Children's Condition and Loving Authority in Johann Friedrich Herbart - Cláudio Almir Dalbosco (Universidade Federal do Rio Grande do Sul, 2018)
This essay investigates how Johann Friedrich Herbart addresses the problem of pedagogical self-government in early childhood education, taking as reference the first book entitled Government of children (Regierung der Kinder) of his work General Pedagogy (Allgemeine Pädagogik), published in 1806. Divided into three parts, the essay examines the Herbartian conception of the child in the first one, and addresses the profile of the educator in the second. Finally, in the third part, it brings some critiques of Herbartian children's pedagogy. An important result of the research is: the active attitude of the educational subject can only be achieved, in the context of early childhood education, when it is grounded in the pedagogy of loving authority.